2014
DOI: 10.2147/ijwh.s54628
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the selection of delivery with no one present in Northern Nigeria: implications for policy and programs

Abstract: This paper examines the effects of demographic, socioeconomic, and women’s autonomy factors on the utilization of delivery assistance in Sokoto State, Nigeria. Data were obtained from the Nigeria 2008 Demographic and Health Survey (DHS). Bivariate analysis and logistic regression procedures were conducted. The study revealed that delivery with no one present and with unskilled attendance accounted for roughly 95% of all births in Sokoto State. Mothers with existing high risk factors, including higher parity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…The low utilization of delivery services at EmOC facilities is reflected in the low proportion of women with direct complications who were treated in EmOC facilities. The present findings are comparable with the results of the Nigeria Demographic and Health Surveys [1,17]—which showed that 62% and 63% of deliveries in 2008 and 2013, respectively, occur at home where many women deliver with nobody else present [18]—and the results reported for most parts of Sub‐Saharan Africa [19].…”
Section: Discussionsupporting
confidence: 91%
“…The low utilization of delivery services at EmOC facilities is reflected in the low proportion of women with direct complications who were treated in EmOC facilities. The present findings are comparable with the results of the Nigeria Demographic and Health Surveys [1,17]—which showed that 62% and 63% of deliveries in 2008 and 2013, respectively, occur at home where many women deliver with nobody else present [18]—and the results reported for most parts of Sub‐Saharan Africa [19].…”
Section: Discussionsupporting
confidence: 91%
“…This finding was consistent with other studies where it has been documented that ethno-religious belief influenced the use of MHS [32][33][34][35][36]. Female autonomy was further reported to be low among the Hausa-Fulani and kanuri/Bari-Bari ethic groups of Northern Nigeria due to adherence to aged long stereotyping as to what is an ideal woman that was based on ethnic and religious norms, beliefs, traditions and practices which was reported to result in low use of MHS and higher incidence of poor pregnancy outcomes in developing [29][30][31][32][33][34][35][36][37][38][39] and developed countries . However, it should be noted that failure to attain the recommended number of ANC visits and to deliver in a health facility will invariably defeat the basic objective of Maternal health Services such as promoting the health of women through health education, counseling, vaccination, family planning, chemo-prophylaxis against malaria, minerals, vitamins and nutritional supplements (iron, and folic acid, screening and early detection of high-risk pregnancies.…”
Section: Discussion On Findingsmentioning
confidence: 99%
“…Details on sampling, training of interviewers, instruments of data collection and data storage were available online in the Demographic and Health report (DHS) [4]. Similar analytical approach using DHS data to determine the variables that influence the use of maternity and child services in Nigeria were conducted [28,29]. The theoretical framework for the study was the Anderson health behaviour model [30,31], which consisted of construct on individual characteristics such as ethnicity/tribe and religion that explains differences in the utilization of health services.…”
Section: Methodsmentioning
confidence: 99%
“…A similar analytical approach using previous Nigerian demographic and health survey data was used to determine the magnitude and factors influencing Maternal and Child Health care Services (MCHCS). 21,22…”
Section: Methodsmentioning
confidence: 99%